A Human Rights based approach to the psychiatric treatment of mental illness among prisoners in Uganda - Jjuuko, Frederick W. (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.